A Case of Refractory Neovascular Glaucoma Treated With a XEN 45 Implant. Issue 10 (October 2018) - Tailor, Rajen; Lalias, Theodoros
Abstract : Neovascular glaucoma carries a poor visual prognosis and surgery is frequently required to control the intraocular pressure. For patients who have visual potential, conventional glaucoma surgery such as a glaucoma drainage device or trabeculectomy are frequently performed. Cyclophotocoagulation is often reserved for eyes with poor visual potential, blind eyes, or where for medical reasons it is not possible for patients to have conventional surgery. Furthermore, patients with neovascular glaucoma often have multiple medical comorbidities, which mean they may be unsuitable for general anesthesia or not able to tolerate lying supine long enough under local anesthesia. We present a case of a patient who was blind in 1 eye from neovascular glaucoma after 2 treatments with cyclophotocoagulation and who then presented with neovascular glaucoma in his only seeing eye. Following failure of cyclophotocoagulation, a Xen implant was performed due to multiple medical comorbitidies, which meant that the patient was not suitable for conventional surgery. Twelve months, after the Xen implant, the patient underwent uncomplicated cataract extraction and lens implant followed by laser capsulotomy at 15 months after Xen implant. At final follow-up (24 months after the Xen implant), the intraocular pressure was 13 mm Hg without glaucoma medication and the patient maintained a corrected vision of 0.0 (6/6 snellen). Our case is the first reported case of the use of the Xen implant in the treatment of refractory neovascular glaucoma. We propose the Xen implant as a potential option in the surgical management of this challenging condition.